2016
DOI: 10.1111/ggi.12868
|View full text |Cite
|
Sign up to set email alerts
|

Frailty syndrome in patients with heart rhythm disorders

Abstract: Frailty syndrome was diagnosed in one-quarter of patients with cardiac arrhythmias, whereas a further 40% were at a higher risk of frailty syndrome, and its occurrence was significantly higher if compared with the control group. Frailty occurred significantly more often among patients with atrio-ventricular blocks, especially in women. The results of the present research showed that there is a statistical association between frailty and arrhythmias. Geriatr Gerontol Int 2017; 17: 1313-1318.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…AF is a common arrhythmia in elderly patients whereas old age and underlying disease in this patient group are associated with a greater mortality and risk of other complications. 20,[26][27][28] In our study, the mean age was 69.8 years, similar to other published studies. 20,[26][27][28][29] On the other hand, old age and AF increase the risk of frailty and significantly contribute to decreased physical and cognitive capabilities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…AF is a common arrhythmia in elderly patients whereas old age and underlying disease in this patient group are associated with a greater mortality and risk of other complications. 20,[26][27][28] In our study, the mean age was 69.8 years, similar to other published studies. 20,[26][27][28][29] On the other hand, old age and AF increase the risk of frailty and significantly contribute to decreased physical and cognitive capabilities.…”
Section: Discussionsupporting
confidence: 91%
“… 20 , 26 – 28 In our study, the mean age was 69.8 years, similar to other published studies. 20 , 26 - 29 On the other hand, old age and AF increase the risk of frailty and significantly contribute to decreased physical and cognitive capabilities. 30 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Frailty syndrome is a state of increased susceptibility to endogenous and exogenous stress factors, which result from reduced physiological reserves and the dysfunction of many of the systems that affect homeostasis and the stress response. 15,16 The literature reports that frailty syndrome is diagnosed in 4.4% to 75.4% of patients with atrial fibrillation. Polidoro et al showed that frailty is an independent factor that is associated with prevalent AF (AF: 89% frail vs no AF: 67% frail).…”
Section: Discussionmentioning
confidence: 99%